2013
DOI: 10.1111/hel.12101
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Method for Evaluation of Gastric Cancer Risk By Serum Markers: Determination of True Low‐Risk Subjects for Gastric Neoplasm

Abstract: Group A included a certain number of patients with atrophic gastritis who were potentially at risk of gastric neoplasm development. Although evaluation of corpus atrophy is necessary for the identification of these patients, the discriminant function may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 27 publications
0
56
1
Order By: Relevance
“…On the other hand, Boda et al reported that more than 10% of gastric cancer patients were classified into group A, suggesting that some patients with gastric cancer risk may be included in group A [12]. Recently, Itoh et al also reported the aberration of high-risk subjects in group A by using radiologic findings [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Boda et al reported that more than 10% of gastric cancer patients were classified into group A, suggesting that some patients with gastric cancer risk may be included in group A [12]. Recently, Itoh et al also reported the aberration of high-risk subjects in group A by using radiologic findings [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the patients in Hiroshima University Hospital, we chose the patients from the database used in the previous study by Boda et al [12]. These 183 gastric cancer patients (136 men; mean age, 66.4 years) with H. pylori-positive results or with CAG were used as controls.…”
Section: Group Bcd Gastric Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, a positive result for serum H. pylori antibody indicates current H. pylori infection. Thus, a gastric cancer screening method using serum anti- H. pylori antibody and PG tests has been applied in some health check-up settings in Japan for screening high risk subjects of gastric cancer, and the method is called as the “ABC method” [6,7,8,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…The main reservoir of H. pylori in humans is the digestive tract, but the bacterium has also been found in biopsy samples, dental plaque, saliva and feces [7]. In recent years, a decrease in the incidence of H. pylori infection in both children and adults has been observed in many countries [8][9][10]. The objective of this study was to estimate the prevalence of H. pylori infection and NHPH infection in symptomatic children over a 13-year study period, and to analyze the resistance rates of H. pylori strains to antibiotics.…”
mentioning
confidence: 99%